SOCIAL PARTNERSHIP IN SOCIAL WORK - Suyumova Markhabo (American Journals Publishing, 2024)
This is in the article, social affairs about information and social of partnership importance as well as social at work social of partnership positive and negative characteristics about data given passed. Both social of partnership time on demand suitable big features about wide data given passed.
Keywords: Social work, country, people, attitude, help, life, well-being.